2017
DOI: 10.1086/690292
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Hypervolumes of Predator Groups and Predator-Predator Interactions Shape Prey Survival Rates and Selection on Prey Behavior

Abstract: Predator-prey interactions often vary on the basis of the traits of the individual predators and prey involved. Here we examine whether the multidimensional behavioral diversity of predator groups shapes prey mortality rates and selection on prey behavior. We ran individual sea stars (Pisaster ochraceus) through three behavioral assays to characterize individuals’ behavioral phenotype along three axes. We then created groups that varied in the volume of behavioral space that they occupied. We further manipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 77 publications
3
20
0
Order By: Relevance
“…Drawing evidence from studies linking animal personality with variation in individuals' ecological niches (Boyer, Réale, Marmet, Pisanu, & Chapuis, 2010; Wilson & McLaughlin, 2007; Wilson et al, 1993), we reason that katydids in groups with high behavioural hypervolumes may associate more closely with one another because of low competition. This is consistent with studies of social heterosis, showing that more behaviourally diverse social groups (Burns & Dyer, 2008; Dyer, Croft, Morrell, & Krause, 2009; Modlmeier & Foitzik, 2011; Modlmeier et al, 2012; Pruitt & Riechert, 2011), nonsocial groups (Pruitt et al, 2017), or even whole communities (Pruitt et al, 2016) compete with each other less and therefore exhibit enhanced collective success. Our study provides some evidence that behavioural hypervolumes can shape the outcome of intraspecific competition in territorial species, like katydids, and may have consequences for their population biology under natural conditions.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Drawing evidence from studies linking animal personality with variation in individuals' ecological niches (Boyer, Réale, Marmet, Pisanu, & Chapuis, 2010; Wilson & McLaughlin, 2007; Wilson et al, 1993), we reason that katydids in groups with high behavioural hypervolumes may associate more closely with one another because of low competition. This is consistent with studies of social heterosis, showing that more behaviourally diverse social groups (Burns & Dyer, 2008; Dyer, Croft, Morrell, & Krause, 2009; Modlmeier & Foitzik, 2011; Modlmeier et al, 2012; Pruitt & Riechert, 2011), nonsocial groups (Pruitt et al, 2017), or even whole communities (Pruitt et al, 2016) compete with each other less and therefore exhibit enhanced collective success. Our study provides some evidence that behavioural hypervolumes can shape the outcome of intraspecific competition in territorial species, like katydids, and may have consequences for their population biology under natural conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Despite this early emphasis on a multitrait approach and the availability of statistical approaches to evaluate multiple behaviours simultaneously, many studies that relate personality to ecological outcomes continue to examine only one trait at a time (Wolf & Weissing, 2012). Here we examine multiple behaviours simultaneously using a recently developed multivariate measure, the behavioural hypervolume (Pruitt, Bolnick, Sih, DiRienzo, & Pinter-Wollman, 2016; Pruitt et al, 2017). …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This assumption includes the caveat that there is no individual heterogeneity among predators or prey (i.e., predators are equally effective in capturing prey, and prey are equally vulnerable to capture) and no interactive effects among predators. However, recent studies have suggested that heterogeneity among predators and predator–predator interactions may generate nonlinear responses in mortality of prey with increasing predator density (Delong & Vasseur, ; Pruitt et al., ; Stallings & Dingeldein, ). Predators can interact with each other as well as with prey to influence mortality among prey via either interference competition or cooperative predation (Delong & Vasseur, ; Stallings & Dingeldein, ).…”
Section: Introductionmentioning
confidence: 99%